2015
DOI: 10.1007/s11999-015-4301-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Peptide IDR-1018 Decreases Implant Infection and Preserves Osseointegration

Abstract: Background Innate defense regulator peptide-1018 (IDR-1018) is a 12-amino acid, synthetic, immunomodulatory host defense peptide that can reduce soft tissue infections and is less likely to induce bacterial resistance than conventional antibiotics. However, IDRs have not been tested on orthopaedic infections and the immunomodulatory effects of IDR-1018 have only been characterized in response to lipopolysacharide, which is exclusively produced by Gram-negative bacteria. Questions/purposes We sought (1) to more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Interestingly, the peptide alone stimulated BMDMs to increase MCP-1 levels comparable to those induced by HKCA treatment. These results are consistent with other studies investigating IDR-1018 in different experimental designs (17,(29)(30)(31). Although our study used a different cell type and inflammatory stimulus, our results indicated that IDR-1018 acts as an anti-inflammatory agent by suppressing proinflammatory cytokines in murine BMDMs challenged with HKCA.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the peptide alone stimulated BMDMs to increase MCP-1 levels comparable to those induced by HKCA treatment. These results are consistent with other studies investigating IDR-1018 in different experimental designs (17,(29)(30)(31). Although our study used a different cell type and inflammatory stimulus, our results indicated that IDR-1018 acts as an anti-inflammatory agent by suppressing proinflammatory cytokines in murine BMDMs challenged with HKCA.…”
Section: Discussionsupporting
confidence: 92%
“…Over the past few decades, the incorporation of antimicrobial agents, including antimicrobial peptides, cationic polymers, and inorganic metallic nanoparticles, at the location of the titanium implants has been sparsely investigated. [15][16][17][18][19][20] These methods have been well established to possess sustained antimicrobial properties. For instance, Chen et al successfully incorporated titanium implant surfaces with an antimicrobial peptide melamine coating that significantly reduced biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the infection surgery did not represent a truly realistic scenario when a single titanium screw would be implanted. Similar models have utilised screws, pins and k-wires to establish an infection (Choe et al, 2015;Li et al, 2008;. However, this limitation was abated by the clinically relevant revision surgery used to treat the established infection.…”
Section: Discussionmentioning
confidence: 99%